PROMOTED ALUMINA SUPPORTED Ni CATALYST FOR ETHANOL STEAM REFORMING - DAN, Monica; MIHET, Maria; LAZAR, Mihaela Diana; MURESAN, Liana Maria (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The catalytic behavior of Ni/γ-Al2O3 catalyst modified with Cu, Ag, and Au was investigated in the process of ethanol steam reforming. The catalysts were prepared by co-impregnation and were characterized by specific surface area determination (SBET), Inductively Coupled Plasma Mass Spectrometry (ICP-MS), X-ray diffraction (XRD), temperature programmed reduction (TPR), temperature programmed desorption (TPD) The data obtained from the experiments revealed that even at a temperature as low as 350°C, the ethanol is converted entirely, showing high selectivity for H2 and CH4.The activity of the Ni/γ-Al2O3 is only slightly increased by the addition of the supplementary metals. Nevertheless, the addition of metals to Ni/γ-Al2O3 has a positive effect in diminishing the quantity of CO2 produced in the reaction. The promoted alumina Ni catalysts present a higher stability in some experimental conditions.